Influences on faculty uptake from a faculty learning community - Bender, Lydia G. (Kansas State University, 2020)
Professional development is a tool that faculty members can use to become more knowledgeable about certain fields of study, or to develop a wide variety of skills. One way that college faculty use professional development is to learn how to become better teachers. We investigate what influences affect the ways in which faculty take up ideas from professional development programs. By employing the framework of Pedagogical Reasoning and Action, we investigate how faculty take up ideas from a particular Faculty Learning Community (the STEM Teaching \& Learning Fellowship) and the factors that influence their instructional and material design choices. Influences affecting faculty were examined in three different cases. From these cases, we constructed themes, and examined those themes across all cases using a cross-case analysis. In this multiple case study we find that alignment between assessment and instruction and participation in departmental practices correspond to the extent in which faculty bring new teaching ideas and practices into the classroom. These findings can be leveraged to help influence the ways in which developers should design and improve programs as well as inform researchers on future avenues of research.
Keywords: Faculty uptake; Pedagogical reasoning and action; Faculty learning community